Handbook of larval amphibians of the United States and Canada - Altig, Ronald; McDiarmid, Roy W. (Comstock Publishing Associates, a division of Cornell University Press, 2015)
Generously illustrated, this essential handbook for herpetologists, ecologists, and naturalists features comprehensive keys to eggs, embryos, salamander larvae, and tadpoles; species accounts; a glossary of terms; and an extensive bibliography. The taxonomic accounts include a summarization of the morphology and basic natural history, as well as an introduction to published information for each species. Tadpole mouthparts exhibit major characteristics used in identifications, and the book includes illustrations for a number of species. Color photographs of larvae of many species are also presented. Handbook of Larval Amphibians of the United States and Canada, written by the foremost experts on larval amphibians, is the first guide of its kind and will transform the fieldwork of scientists and fish and wildlife professionals.